PERTUMBUHAN ITIK BALI JANTAN UMUR DUA SAMPAI DELAPAN MINGGU YANG DIBERI RANSUM DENGAN BIOSUPLEMEN MENGANDUNG BAKTERI SELULOLITIK UNGGUL ASAL RAYAP - I G. P. A. A., Saputra; Dewi, G. A. M. K.; Mudita, I M. (Jurnal Peternakan Tropika, 2016)
The research has been carried out to evaluating the growth of bali drake aged two until eight weeks given ration supplemented with biosupplement containing preeminent cellulolytic bacteria isolated from termitesin Peguyangan Kaja Village, Denpasar Utara Subdistrict, Denpasar for twelve weeks. Bacteria isolates used in this research were first and second preeminent probiotic cellulolytic bacteria isolated from termites with coded BR3.3 and BR3.5. Completely Randomized Design (CRD) consisted five treatments and three replicates were enployed. The fisrt treatment was basal ration without supplemented (RS0), while the other treatments were ration supplemented biosupplement without termites preeminent cellulolytic bacteria (RSBio0), Ration supplemented with biosupplement containing termites first preeminent cellulolytic bacteria (RSBio1), Ration supplemented with biosupplement containing termites second preeminent cellulolytic bacteria (RSBio2), and Ration supplemented with biosupplement containing first and second preeminent cellulolytic bacteria from termites (RSBio1-2). The observed variables in the research were commencing body weight, final body weight, body weight gain, feed consumption, and Feed Conversion Ratio (FCR). The result showed that baliness duck given ration supplementated with biosupplement containingtermites first or seconds preeminent cellulolytic bacteria (RSBio1 and RSBio2) can increasing (P 0,05). While for feed consumption, all treatments has not significant different (P>0,05). It was concluded that baliness duck given ration supplemented with biosupplemented containing first or second preeminent cellulolytic bacteria from termites can increasing final body weight, body weight gain, and efficiency of feed usage with relative same for feed consumption.
Keywords: preeminent cellulolytic bacteria of termites, biosupplement, bali drake, growth